2013
DOI: 10.3807/josk.2013.17.1.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Luminous Efficiency of Phosphor-Conversion White Light-Emitting Diode

Abstract: The author analyzes the luminous efficiency of the phosphor-conversion white light-emitting diode (LED) that consists of a blue LED chip and a yellow phosphor. A theoretical model is derived to find the relation between luminous efficiency (LE) of a white LED, wall-plug efficiency (WPE) of a blue LED chip, and the phosphor absorption ratio of blue light. The presented model enables to obtain the theoretical limit of LE and the lower bound of WPE. When the efficiency model is applied to the measured results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…CDAM mainly consists of narrow-band LED [25,26] light sources, reflective neutral attenuators with known attenuation coefficients (given by the manufacturer), and a photomultiplier (PMT). The basic principle is based on the substitution method, using the attenuation coefficients of the standard reflective neutral attenuators (SRNAs) as references.…”
Section: Introductionmentioning
confidence: 99%
“…CDAM mainly consists of narrow-band LED [25,26] light sources, reflective neutral attenuators with known attenuation coefficients (given by the manufacturer), and a photomultiplier (PMT). The basic principle is based on the substitution method, using the attenuation coefficients of the standard reflective neutral attenuators (SRNAs) as references.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependence of the WPE of the blue LED and that of PCE are determined separately from spectral analyses, which are used to explain the temperature dependence of LE in the white LED. It is not easy to evaluate the absolute value of PCE for the phosphor material in the white LED [6]; nevertheless, it will be shown that the relative change of PCE with temperature can be obtained through the analysis of the LED's efficiency and spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The CRI value of the high power white LEDs has been increased due to development of phosphors that convert the blue LED lights into white light. [2,3] Besides the high CRI values, high illuminance is also required in the dental astral lamp. More specifically, the dental astral lamps require 10,000 lx for diagnosis and 2~40,000 lx for dental surgery.…”
Section: Introductionmentioning
confidence: 99%